How big is it? : a big book all about BIGness - Hillman, Ben, 1957- (New York : Scholastic Reference, 2007)
1. Size perception--Juvenile literature
Giant squid: Lengthy leggy leviathan -- Olympus mons: Biggest volcano in the solar system -- Reticulated python: Longest snake -- Quetzalcoatlus: Biggest animal that ever flew -- Great pyramid at Giza: Wonder of the ancient world -- Goliath bird-eating spider: Biggest, creepiest arachnid -- Tsunami: Highest wave -- Polar bear: Biggest living carnivore -- Dragonfly of the carboniferous: Biggest flying insect -- Ice age glacier: Gigantic ice sheet -- Airship: Biggest flying machine -- Dinosaur-killing asteriod: Giant rock from outer space -- Egg of the elephant bird: Largest egg in history -- Redwood: Tallest living thing -- Akula (shark) submarine: Biggest diving machine -- Giraffe: Tallest living animal -- Arecibo radio telescope: Biggest dish -- Diamond: Too big for your finger -- Valles Marineris: Biggest crack in the solar system -- Flower: Biggest, weirdest flower -- Eta Carinae: Enormous star -- Googol: Extremely gigantic humongous insanely large number.
Includes index.
Basic Ed. Students
Keywords: Size perception -- Juvenile literature; Size judgment -- Juvenile literature; Size